Are placebo controls necessary in controlled human infection trials for vaccines?. Issue 4 (April 2020) - Langenberg, Marijke C C; Dekkers, Olaf M; Roestenberg, Meta
Summary: Controlled human infection trials, whereby a small group of healthy participants is deliberately exposed to a pathogen under controlled circumstances, can provide preliminary data for vaccine efficacy and for the selection of the most promising candidate vaccines for field trials. Because of the potential harm to participants through the deliberate exposure to a pathogen, the use of smaller groups minimises the cumulative risk. As such, a control group that receives a placebo vaccine followed by controlled exposure to a pathogen should be scientifically well justified. As these types of trials are designed to generate consistent infection rates and thus comparable outcomes across populations and trial sites, data from past studies (historical data) could be used as a valid alternative to placebo groups. In this Personal View, we review this option and highlight the considerations for choosing historical data as a suitable control. For the widespread application of this method, responsibility for the centralisation and sharing of data from controlled human infection trials lies with the scientific community.